PENENTUAN JARAK OPTIMAL ANTARA HELM DAN KEPALA DARI SUDUT PANDANG KENYAMANAN THERMAL PADA HELM TENTARA - , ANDUNG JATI NUGROHO, Ir. Heru Santoso B.R., M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Helmets are known as one of the military basic uniform. Helmet is a form of protective gear worn on the head to protect it from injuries, others than that helmet has to be comfortable. As personal protective equipment, a combat helmet or a battle helmet is a type of personal armor designed specifically to protect the head during a fight. And comfortable means fits perfectly when they wearing it. In order to get ergonomics there have been researching about the proper ergonomic design between helmet and head for military helmet. On the research first thing that we have done was validating between measurements using modeling method on the standard combat helmet and measurements using experiment method on the standard combat helmet. Validation of a measuring modeling method has been done by creating a geometrical model of standard combat helmet with Gambit 2.4.6 software, and then analyzed with Fluent 6.3.26 software by considering at 1,6 m/s wind speed and at 310C environment temperature. Meanwhile validation of a measuring experiment method has been done by picking 5 sample experiments up, in which direct measuring on between helmet and head temperature have been done at 3 observation points. After there was validity on the model helmet, and then creates 10 geometrical model helmets at 0,6 cm minimum space distance by creating various distance at 0,3 cm multiplication using Gambit 2.4.6 software. Analyze the geometrical result using Fluent 6.3.26 software on to these 10 geometrical models considering other factors like environments temperature, wind speed, and humidity (H2O mole fraction). The research conclusion shows that in the distance 0,9 cm is the optimum distance with other factors like the motions of air between helmet and head, temperature and H2O mole fraction. Therefore to design a military helmet, the best way if there are improvement in quality and ergonomic and also considering thermal comfort in every designs.